PENGARUH DEBT TO ASSET RATIO (DAR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON EQUITY (ROE) PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siti Fatonah; Siti Nuradila Amini; Bambang Tri Dayono (Universitas Bina Bangsa, 2022)
This study aims to determine the effect of Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) on Return On Equity (ROE) in Food and Beverage Companies listed on the Indonesia Stock Exchange for the 2015-2021 period. The research method used is causal associative method with quantitative research using secondary data in the form of financial report data obtained from www.idx.co.id and www.idnfinancial.com. The population in this study is the Food and Beverage Sub-Sector Companies listed on the Indonesia Stock Exchange for the 2015-2021 period, totaling 32 companies. The sample in this study were 6 companies with purposive sampling technique.The results of this study indicate that the partial t-test Debt to Asset Ratio has no effect on Return On Equity with a value of tcount < ttable (1.108 < 2.021) and a significant value of (0.275 > 0.05). Debt to Equity Ratio (DER) has a significant effect on Return On Equity (ROE) with a value of tcount > ttable (22,977 > 2.021) and a significant value of (0.000 < 0.05). By simultaneous f-test, Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) have a significant effect on Return On Equity (ROE) with fcount > ftable (264.314 > 3.24) and significant value (0.000 < 0.05) ).The conclusion of this study is that partially Debt to Asset Ratio has no effect on Return On Equity, Debt to Equity Ratio has an effect on Return On Equity and simultaneously (simultaneously) Debt to Asset Ratio and Debt To Equity Ratio affect Return On Equity in Food and Beverage Companies Listed on the Indonesia Stock Exchange for the 2015-2021 Period